The Effect of Primigravida Mother's Perineal Massage on Perineal Rupture in Tutun Sehati Pratama Clinic, Tanjung Morawa District Deli Serdang Year 2021 - Asnita Sinaga (Institute of Computer Science (IOCS), 2022)
The incidence of perineal tears needs to be prevented, one of which is by doing perineal massage. Perineal massage is one way to increase blood flow, elasticity, and relaxation of the pelvic floor muscles (Mogan, 2013). According to the World Health Organization (WHO), the maternal mortality rate in the world in 2015 was 2016 per hundred live births or it is estimated that the number of maternal deaths was 303,000 deaths with the highest number being in developing countries, which was 302,000 deaths. The type of research conducted is qualitative research with quasi-experimental research design with post-test only with group design. The results of the study The majority in the intervention group did not rupture, namely 18 respondents (45%), the control group 3 respondents (7.5), the intervention group ruptured 2 (5%), the rupture control group 17 (42.5%), chi-test square the effect of perineal massage on rupture in the intervention group and the control group, it was found that the p(sig) value was 0.000 < 0.05. this can be interpreted that there is an effect of perineal massage for primigravida mothers on perineal rupture at the Tutun Sehati Primary Clinic, Tanjung Morawa District. There is an effect of perineal massage for primigravida mothers on perineal rupture at the Tutun Sehati Primary Clinic, Tanjung Morawa District, Deli Serdang Regency in 2021.